2016
DOI: 10.1155/2016/8970291
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant Immune- and Apoptosis-Related Gene Expression Is Associated with Kidney Allograft Function

Abstract: Renal transplant candidates present immune dysregulation, caused by chronic uremia. The aim of the study was to investigate whether pretransplant peripheral blood gene expression of immune factors affects clinical outcome of renal allograft recipients. Methods. In a prospective study, we analyzed pretransplant peripheral blood gene expression in87 renal transplant candidates with real-time PCR on custom-designed low density arrays (TaqMan). Results. Immediate posttransplant graft function (14-day GFR) was infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Studies have suggested that IL-18 with NGAL and creatinine are the most sensitive markers of DGF [ 40 ]. Moreover, IL-18 positively correlates with kidney function at 6 and 24 months after transplantation [ 41 ]. Urine-detected IL-18 is an early diagnostic marker of acute kidney injury (AKI), and it precedes symptoms by 24–48 h [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that IL-18 with NGAL and creatinine are the most sensitive markers of DGF [ 40 ]. Moreover, IL-18 positively correlates with kidney function at 6 and 24 months after transplantation [ 41 ]. Urine-detected IL-18 is an early diagnostic marker of acute kidney injury (AKI), and it precedes symptoms by 24–48 h [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pretransplant peripheral blood TGF-β gene expression was found to negatively influence immediate post-transplant kidney allograft function [ 128 ]. Compared with normal kidney tissue, a high gene expression of TGF-β1 was identified in kidneys retrieved from brain dead donors.…”
Section: Biomarkers Of Kidney Injury Progressionmentioning
confidence: 99%
“…These studies have been more commonly performed on renal biopsy samples as they provide sufficient material for RNA extraction. As listed in Table 1, gene signatures associated with fibrosis, i-IFTA, chronic rejection (ABMR and TCMR) and graft failure can be identified by determining gene expression profiling (45)(46)(47)(48)(49)(50)(51)(52)(53). Importantly, the gene set has higher predictive capacity than that of baseline clinical variables, and clinical and pathological variables.…”
Section: Transcriptomic Biomarkersmentioning
confidence: 99%